How can Universities Transition to Net Zero? - Breadsell, Jessica; Minunno, Roberto (Architectural Science Association, 2021)
INTRODUCTION: Australian Universities have been investigating reducing carbon emissions for over a decade, with many implementing energy efficiency measures and renewable energy systems on their campuses. As of February 2021, 23 out of 40 Universities in Australia have committed to some form of climate action targets (100% Renewables, 2021). In addition to setting organisational targets to reduce carbon, Universities can support and engage with their own employees to undertake net zero research projects. These may be based on the campus, transforming the space into a living laboratory—a space of innovation—or it can be through supporting academics researching in the net zero space with targeted grant money or support. This abstract will discuss three such projects that Curtin University has been involved with over the last few years: The Green Wave, The Legacy Living Lab (L3; https://l3.curtin.edu.au/) and Curtin Net Zero Research Projects. METHODS: The Green Wave project was a 6-month cross institutional research project on how Universities can undertake net zero energy and decarbonisation strategies whilst more deeply engaging community and business partnerships to deliver greater trust, legitimacy and social value. Curtin researchers worked with Monash University and University of Technology Sydney, all at different stages of committing to net zero targets, to investigate what initiatives could be undertaken by the University to further decarbonisation actions. The L3 is a living lab developed with 26 industry partners around the circular economy concept at Curtin University. L3 showcases how reused materials and designing for disassembly can coexist with a net zero building. L3 features 8kW of solar panels, connects to a 670kWh communal battery and is now testing the use of automatic blinds, smart lights, temperature and brightness sensors and air quality monitoring in operation. The Curtin Net Zero Research Projects are a group of 14 research projects undertaken in the second half of 2021 that investigate a range of net zero related areas, ranging from understating the historical evolution of net zero, understanding how new technologies in the built environment, transport and food sectors can contribute to net zero targets and how occupancy of buildings can be optimised to enable improved energy efficiency. The researchers involved are from the Faculties of Humanities, Business and Law and the Centre for Aboriginal Studies. RESULTS: Institutions such as universities play a unique role in addressing the net zero challenge through their own scope 1, 2 and 3 emissions. Overall, the initiatives undertaken are similar to other organisations worldwide, with only some focus on universities unique role as education institutions considered in the implementation of targets. However, far greater impacts can be achieved by looking to influence the emissions of those within the institution’s sphere of influence: staff, students, local community and supply chains. The L3 building is used as a testbed of extensive research to create more profound interconnections between the multiple devices. This interconnection aims towards an intelligent management system that can suggest to the users the best strategies towards energy saving – not only from the building but also from the grid’s needs and loads. Thus far, this research has resulted in identifying several issues with how smart devices need to intercommunicate to work effectively together such as the smart blinds and temperature sensors not communicating and the different needs of the office workers in the space. The Curtin Net Zero Research Projects are situated across five research areas: transport, the built environment, energy, food and materials. The initiative supports the ongoing SDGs strategy for Curtin, the ongoing Energy Institute taskforce and Curtin’s aspiration for Net Zero. Fostering interaction between researchers of different disciplines has enabled clearer connections to form and highlight opportunities for future research on fostering the net zero transition across society. The project is raising the profile of net zero research in this space and creating opportunities for collaboration and knowledge sharing to accelerate the impact of research. CONCLUSIONS: Some Universities have focused on their unique attributions as research and teaching organisations to differentiate their net zero plans from other organisations. The use of campus’ as living laboratories, including buildings such as L3, to monitor emissions and test initiatives have enabled some universities to decarbonise whilst also supporting their researchers. By integrating net zero and other sustainability themes into their two core businesses—research and education—universities can extend their impact to develop practical and innovative climate change solutions.